Improving The Learning Concentration Of Children Aged 4-5 Years Through The Tebona Game Method (Patting Colored Balls) In TK Aisyiyah Bustanul Athfal 3 Bulusidokare: Meningkatkan Konsentrasi Belajar Anak Usia 4-5 Tahun Melalui Metode Permainan Tebona (Tepuk Bola Warna) Di TK Aisyiyah Bustanul Athfal 3 Bulusidokare - Izatul Fikro; Agus Salim (Academia Open, 2023)
Learning concentration is an important component in the learning process, with high learning concentration for each child, it will be able to support the child to be ready for further education. This research aims to increase the learning concentration of children aged 4-5 years through the tebona game method (patting colored balls) at Aisyiyah Bustanul Athfal 3 Bulusidoakre Kindergarten. This type of research uses classroom action research (PTK), the design used in this research is the Kemmis and Mc Taggrat model of classroom action research design. The subjects of this research were 10 students in group A3 aged 4-5 years, children. Data collection techniques by means of observation, documentation and interviews. The results of the research show that children's learning concentration increases in each cycle. Before the action, the concentration percentage only reached 46% in the pre-cycle, 66.5% in cycle 1 and 94.5% in cycle II. So it can be concluded that increasing the learning concentration of children aged 4-5 years through the tebona playing method at Kindergarten Aisyiyah Bustanul Athfal 3 Bulusidokare was declared successful. Highlights: Importance of Learning Concentration: Learning concentration is crucial for children's readiness for further education. Tebona Game Method: Tebona game method involves patting colored balls to enhance concentration. Classroom Action Research (PTK): PTK design allows for systematic observation and assessment of educational interventions. Keywords: Learning Concentration, Tebona Games, Early Childhood